2022
DOI: 10.1002/sim.9643
|View full text |Cite
|
Sign up to set email alerts
|

A likelihood‐based sensitivity analysis for publication bias on the summary receiver operating characteristic in meta‐analysis of diagnostic test accuracy

Abstract: In meta‐analysis of diagnostic test accuracy, the summary receiver operating characteristic (SROC) curve is a recommended method to summarize the diagnostic capacity of a medical test in the presence of study‐specific cutoff values. The SROC curve can be estimated by bivariate modeling of pairs of sensitivity and specificity across multiple diagnostic studies, and the area under the SROC curve (SAUC) gives the aggregate estimate of diagnostic test accuracy. However, publication bias is a major threat to the va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…16,17 In many published metaanalyses of DTA, the presence of PB was tested by the asymmetry of the funnel plot on the log-transformed diagnostic odds ratio (lnDOR), which suggested that the -statistic of the lnDOR might be responsible for the underlying selective publication. Zhou et al 10 proposed the cutoff-dependent selection function to model different selective publication mechanisms and extended the likelihood-based sensitivity analysis for PB in meta-analysis of intervention studies 17 into meta-analysis of DTA. The method of Zhou et al adopted a general class of selection functions on the linear combination of logit-transformed sensitivity and specificity, which included the lnDOR as the special case.…”
Section: A Brief Review Of the Likelihood-based Sensitivity Analysis ...mentioning
confidence: 99%
See 4 more Smart Citations
“…16,17 In many published metaanalyses of DTA, the presence of PB was tested by the asymmetry of the funnel plot on the log-transformed diagnostic odds ratio (lnDOR), which suggested that the -statistic of the lnDOR might be responsible for the underlying selective publication. Zhou et al 10 proposed the cutoff-dependent selection function to model different selective publication mechanisms and extended the likelihood-based sensitivity analysis for PB in meta-analysis of intervention studies 17 into meta-analysis of DTA. The method of Zhou et al adopted a general class of selection functions on the linear combination of logit-transformed sensitivity and specificity, which included the lnDOR as the special case.…”
Section: A Brief Review Of the Likelihood-based Sensitivity Analysis ...mentioning
confidence: 99%
“…The method of Zhou et al introduced the marginal selection probability, = (publish), as the sensitivity parameter, which implies the expected proportion of the published studies from the population of all studies. Given a range of values of , the SROC curves and the corresponding SAUC accounting for PB could be estimated from the conditional log-likelihood of the observed data (equation 13 in Zhou et al 10 ). Under the flexible selective publication mechanisms driven by the contrast ( 1 , 2 ) and a range of 's, the impact of PB could be assessed by the changes of the estimated SROC curves and SAUC.…”
Section: A Brief Review Of the Likelihood-based Sensitivity Analysis ...mentioning
confidence: 99%
See 3 more Smart Citations